Spatial variability of CO2 emission, temperature and moisture of a bare oxisol submitted to different wetting levels - Panosso, Alan Rodrigo [UNESP]; Ribeiro, Carlos Eduardo Rodrigues [UNESP]; Zanini, José Renato [UNESP]; Pavani, Luiz Carlos [UNESP]; Pereira, Gener Tadeu [UNESP]; La Scala Jr., Newton [UNESP] (Universidade Estadual de Londrina, 2009)
The irrigation application is one of the most useful techniques in tropical environments, especially during dry seasons. In this study, CO2 efflux, temperature and soil moisture were studied in a field sampled with a grid having 48 points distributed in 35 × 25 m, under irrigation promoted by a sprinkler located at the center of the area, provoking different levels of water deposition, with maximum irrigation levels of 44.4 and 62.2 mm in points closer to the sprinkler. The results show that the emissions, temperature and moisture were strongly affected by the two irrigations events, having a total water level added of 106,6 mm for the points next to the sprinkler and zero for the most distant points from it. The maps of space variation of the variables, as well as the linear correlation between them, indicate that the emissions were positively related to the soil moisture and negative correlated to the soil temperature only after the irrigations events. The special variability models of soil CO2 emission changed from exponential to spherical after the irrigations events. Such results indicate that soil moisture is among possible controlling factors of the soil CO2 emission, because even with reductions in soil temperature provoked by the wetness, emissions increased strongly.
Variabilidade espacial da emissão de CO2, da temperatura e umidade de um latossolo desprovido de vegetação sob diferentes lâminas de molhamento
Keywords: Geostatistics; Sprinkler irrigation